International and Indian Civil Liability Regime for Nuclear Damage - Operator’s Liability v. Supplier’s Liability - Chandalia, Sidhant (Kathmandu School of Law Review, 2011)
Nuclear energy has seen tremendous growth in the last two decades and has a considerable share in world electricity supply. No nuclear reactor can be 100 % safe. Every reactor has a small, but finite chance of catastrophic failure, as seen in Chernobyl, Three Mile Island, Fukushima and many smaller accidents around the world, including those in India. Nuclear projects are non-bankable in the sense that they cannot be insured. If they could, the matter would be simple enough. The nuclear plant and every person likely to be affected by radiation would be insured for a suitable sum, but the cost of a disaster and the lawsuits that would ensue make it virtually impossible to insure a nuclear power plant. Hence, there is a need to put an artificial compensation and liability mechanism in place to deal with nuclear accidents. The issue is not merely the amount of compensation to be paid in the event of an accident but also who would be encumber with the bill, the operators or the suppliers, and to what extent.